Estrutura de mercado: uma análise do impacto da presença ascendente de bancos 100% digitais na indústria bancária brasileira. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The present dissertation aims to analyze the impact of the digital banks growth on the market structure of the Brazilian banking industry from the perspective of concentration, using the normalized Herfindahl-Hirschman Index, and competition, using the methodology of H statistic from Panzar-Rosse. It is also elaborated a brief discussion on the distribution of bank agencies in the Brazilian territory, as well as a summarized analysis of the regulations promoted by the Central Bank to promote deconcentration and encourage competition in this sector. The variables used were arranged in an unbalanced panel containing 159 financial institutions operating in Brazil between the first quarter of 2000 and the fourth quarter of 2019. The results obtained point out to a market with characteristics of monopolistic competition and moderate levels of concentration, in addition is show a prospect of improvements on the concentration and competition levels, given to the growth number of digital banks in the market
Keywords: Concentração; Competição; Indústria Bancária; Bancos Digitais; Concentration; Competition; Banking Industry; Digital Banks; CNPQ::CIENCIAS SOCIAIS APLICADAS::ECONOMIA